2000
DOI: 10.1103/physreva.62.033606
|View full text |Cite
|
Sign up to set email alerts
|

Quantum kinetic theory. VI. The growth of a Bose-Einstein condensate

Abstract: A detailed analysis of the growth of a Bose-Einstein condensate is given, based on quantum kinetic theory, in which we take account of the evolution of the occupations of lower trap levels, and of the full Bose-Einstein formula for the occupations of higher trap levels, as well as the Bose-stimulated direct transfer of atoms to the condensate level introduced by Gardiner et al. ͓Phys. Rev. Lett. 79, 1793 ͑1997͒; 81, 5266 ͑1998͔͒. We find good agreement with experiment at higher temperatures, but at lower tempe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 27 publications
3
67
0
Order By: Relevance
“…Other approaches to incorporate the thermal cloud include Stoof's nonequilibrium theory based on quantum kinetic theory [514][515][516][517] and Gardiner-Zoller's quantum kinetic master equation using techniques borrowed from quantum optics [518][519][520][521][522][523][524]. Also, efforts to include stochastic effects have been considered in Ref.…”
Section: Beyond Mean-field Descriptionmentioning
confidence: 99%
“…Other approaches to incorporate the thermal cloud include Stoof's nonequilibrium theory based on quantum kinetic theory [514][515][516][517] and Gardiner-Zoller's quantum kinetic master equation using techniques borrowed from quantum optics [518][519][520][521][522][523][524]. Also, efforts to include stochastic effects have been considered in Ref.…”
Section: Beyond Mean-field Descriptionmentioning
confidence: 99%
“…For the purpose of comparing the influence of the slab length on the thermalization dynamics, we choose the same logarithmic scale for all vertical axes. The discussion before (137) showed that exact agreement with the Maxwell-Boltzmann distribution is only achieved for z → ∞, whereas the contribution to thermalization is most pronounced where the particle density is highest, i. e. in the first half of the slab.…”
Section: Spectral Flux Density Inside the Slab And The Creation Of A mentioning
confidence: 99%
“…As a consequence, we expect the particle flux incident on the slab to equilibrate towards the distribution (137), provided the slab is sufficiently long. However, before scrutinizing this prediction numerically, we come back to the diagrammatic Gross-Pitaevskii equation: In which limit does our result (123) reproduce the stable coherent state described by the Gross-Pitaevskii equation, rather than thermalization?…”
Section: Particle and Energy Flux Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…A relevant-and analytically tractable-mean-field model that has recently gained attention in the study of temperatureinduced dissipation of dark solitons [18,20,[22][23][24][25] is the so-called dissipative Gross-Pitaevskii equation (DGPE). This model, which was first introduced phenomenologically [26] and later was justified from a microscopic perspective [27], has also been used in other works to describe, e.g., decoherence [28] and growth [29] of BECs, damping of collective excitations of BECs [30], vortex lattice growth [31,32], vortex dynamics [33][34][35][36], and dynamics of quasicondensates [37]. In the case of dark solitons, the DGPE model can describe accurately finite-temperature-induced soliton decay: results stemming from a perturbative study of soliton dynamics in the framework of the DGPE, compares favorably to ones obtained by the more accurate stochastic Gross-Pitaevskii model [20,22,23] (the latter, is a grand-canonical theory of thermal BECs, containing damping and noise terms which describe interactions of low-energy atoms with a high-energy thermal reservoir-see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%